ANALYSIS FACTORS AFFECTING DECISION TO USE SERVICES IN LEARNING GUIDANCE INSTITUTIONS - Sunia Risdiani; Rusdianto Rusdianto (Value : Jurnal Manajemen dan Akuntansi, 2023)
This research is motivated by the intense competition in the service business so that companies can see the direction and purpose of the products they want to offer. This study aims to explain (1) Does the price variable affects the decision to use tutoring services. (2) Does the service quality variable affects the decision to use guidance services. (3) Does the program quality variable affects the decision to use tutoring services. The sample used in this study was 35 respondent; this study was based on primary data obtained through distributing questionnaires. This sampling technique uses a proportionate stratified random sampling technique, a population with heterogeneous and proportionally equalized members or elements. The data processing method in this study is to use multiple linear analysis using the SPSS 23 analysis tool. The results showed that Price, Service Quality and Program Quality had no positive and insignificant effect on decision to use services. Keywords: Price, Service Quality, Program, Decisions